2019
DOI: 10.3390/toxins11080471
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Ochratoxin A (OTA), Ochratoxin B (OTB), T-2, and HT-2 Toxins in Wheat Grains, Wheat Flour, and Bread in Lebanon by LC-MS/MS

Abstract: Cereals are prone to fungal infection during growth, harvesting, transportation, and/or storage. As a result, cereals such as wheat grains and wheat-derived products may be contaminated with mycotoxins leading to acute and chronic health exposure. The current study investigated the presence of the mycotoxins: ochratoxin A (OTA), ochratoxin B (OTB), T-2, and HT-2 toxins in samples of wheat grains (n = 50), wheat flour (n = 50), and bread (n = 37) from the main mills in Lebanon using LC-MS/MS. Accuracy ranged fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(12 citation statements)
references
References 63 publications
0
11
1
Order By: Relevance
“…Joubrane et al [ 34 ] recorded that 28.21 % of wheat samples collected during the 2008 cultivation season from Lebanon were contaminated with OTA at concentrations (>3 μg/kg), while 19.20 % of wheat samples collected during the 2009 cultivation season were contaminated with OTA at concentrations (>3 μg/kg). Recently, Elaridi et al [ 46 ] revealed that OTA was not detected in wheat samples obtained from Lebanon. The situations of the grains at harvest depend on, how carefully the grains are dried, and on the storage conditions [ 47 ].…”
Section: Resultsmentioning
confidence: 99%
“…Joubrane et al [ 34 ] recorded that 28.21 % of wheat samples collected during the 2008 cultivation season from Lebanon were contaminated with OTA at concentrations (>3 μg/kg), while 19.20 % of wheat samples collected during the 2009 cultivation season were contaminated with OTA at concentrations (>3 μg/kg). Recently, Elaridi et al [ 46 ] revealed that OTA was not detected in wheat samples obtained from Lebanon. The situations of the grains at harvest depend on, how carefully the grains are dried, and on the storage conditions [ 47 ].…”
Section: Resultsmentioning
confidence: 99%
“…used salting‐out assisted liquid–liquid extraction (SALLE) coupled with high‐performance liquid chromatography–mass spectrometry (HPLC–MS) to detect OTA in beer samples, revealing a detection limit of 0.02 ng mL −1 14 . The established HPLC‐tandem mass spectrometry (MS/MS) method used for the simultaneous detection of OTA, ochratoxin B (OTB), and T‐2 toxin in wheat products has a limit of detection (LOD) of 0.12 ng mL −1 for OTA 15 . Sun et al .…”
Section: Introductionmentioning
confidence: 99%
“…14 The established HPLC-tandem mass spectrometry (MS/MS) method used for the simultaneous detection of OTA, ochratoxin B (OTB), and T-2 toxin in wheat products has a limit of detection (LOD) of 0.12 ng mL −1 for OTA. 15 Sun et al developed a graphene aptamer platform based on electrochemical analysis to detect OTA with a LOD of 5.6 pg mL −1 . 16 Many immunoassays have also been developed for the detection of OTA.…”
Section: Introductionmentioning
confidence: 99%
“…According to the International Agency for Research on Cancer (IARC), OTA has been classified as a group 2B carcinogen ( 4 , 5 ). It was observed that there was an occurrence of renal tumors when the dietary intake was more than 70 μg/kg of OTA per day in humans ( 6 ). In chicken farms, feeding OTA-contaminated feed at a rate of 0.025 g/kg over an extended period of time may result in tumour progression in the liver, kidneys, ureters, or spleen ( 7 ).…”
Section: Introductionmentioning
confidence: 99%